Effects of vitamin C dosage levels on growth and survival rate of sidat fish (Anguilla bicolor, McClelland, 1844) - Muamar, Abdan; Hasri, Iwan; Harun, Harun; Suprihadi, Suprihadi; Saputra, Fazril; Fahmi, Rizkan; Hardiansyah, Hardiansyah (Universitas Malikussaleh, 2024)
Eel is a species with high economic value, but its slow growth and low survival rate are problems that need to be addressed through the development of effective cultivation technology. This study aimed to investigate the effects of vitamin C dosage on the growth and survival of eels (Anguilla bicolor). This study was conducted at the UPR. Mina Mandiri, Beutong District, Nagan Raya Regency, during the period August to October 2023. The method used was a completely randomized design with four treatment levels and three replications, namely 0, 200, 300, and 400 mg/kg feed. ANOVA results showed that the dose of vitamin C had a significant effect on the growth and survival of eels (P < 0.05). Further tests using Duncan's method showed significant differences between treatments in growth parameters, but there was no significant difference in survival. The 200 mg/kg feed dose showed the highest and optimal results in terms of increasing the growth and survival of eel fish.Keywords: Culture technology; eel; growth; vitamin C